Motor Skills Training in Orthopedic Sports Medicine - Karahan, Mustafa; Espregueira-Mendes, João; Akan, H. Kaya (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book aims to provide orthopedic surgeons with all the information that they will require in order to set up and run a motor skills course that will meet the needs of junior staff in Orthopedic Sports Medicine and help in training better surgeons for the future. The coverage is wide-ranging, from the fundamentals of what it takes to be a sports surgeon through to validation methods that measure teaching effectiveness and the certification of surgical skills at the end of the course. Clear guidance is provided on how to teach concepts of surgical skill and the strategy and practical details of designing a training program, with inclusion of a helpful checklist of do's and don'ts. Different basic training modalities are described, with a particular focus on the FAST system adopted by the Arthroscopy Association of North America, and the role of simulators in surgical skills training is discussed. The book has been produced in cooperation with ISAKOS and the authors are leading professionals from around the world who offer a truly global and multidisciplinary perspective on the subject.